Are risk factors of cerebral small vessel disease differ from those in patients with high atherothrombotic risk without cerebrovascular disease? - Staszewski, Jacek; Skrobowska, Ewa; Piusińska-Macoch, Renata; Brodacki, Bogdan; Stępień, Adam (Journal of Medical Science, 2018)
Knowledge of risk factors for cerebral small vessel disease (CSVD) may generate hypothesis regarding possible targets for prevention. Our aim was to evaluate if atherothrombotic risk factors differ between patients with CSVD and with subjects without cerebrovascular disease but with high cardiovascular (CVD) risk. A single-center, cohort study was performed in consecutive patients with different CSVD manifestations. The study group consisted of 205 patients: 52 with lacunar stroke (LS), 20 with subcortical hemorrhagic stroke (HS), 50 with vascular dementia (VaD), 28 with vascular parkinsonism (VaP) and 55 controls (CG) with high CVD risk (35 with atherosclerotic CVD, 20 with 10-year risk of CVD with SCORE?5). Logistic regression was used to analyze the influence of clinical and laboratory data on the occurrence of CSVD. Mean age, sex distribution, prevalence of smoking, hyperlipidemia, peripheral artery disease and obesity were similar in CSVD and CG. The factors significantly associated with CSVD compared to controls were diabetes mellitus, polymetabolic syndrome, elevated systolic blood pressure, low levels of eGFR, HDL, albumin and high uric acid, fibrinogen, fasting glucose, HbA1c and intima medic thickness (p<0.05). Hypertension, chronic kidney disease and elevated fasting blood glucose were related to LS and HS (p<0.1). Diabetes was significantly associated with LS and VaD while smoking and low total cholesterol were related to HS (p<0.1). The study confirms that risk factors profile for CSVD differs from subjects with proatherogenic profile without history of cerebrovascular disease. Our results also support that unique risk factors profiles exist for different manifestations of the CSVD.